Different roles of T-type calcium channel isoforms in hypnosis induced by an endogenous neurosteroid epipregnanolone. (1st October 2021) - Coulter, Ian; Timic Stamenic, Tamara; Eggan, Pierce; Fine, Brier R.; Corrigan, Timothy; Covey, Douglas F.; Yang, Lingling; Pan, Jen Q.; Todorovic, Slobodan M.
Abstract: Background: Many neuroactive steroids induce sedation/hypnosis by potentiating γ-aminobutyric acid (GABAA ) currents. However, we previously demonstrated that an endogenous neuroactive steroid epipregnanolone [(3β, 5β)-3-hydroxypregnan-20-one] (EpiP) exerts potent peripheral analgesia and blocks T-type calcium currents while sparing GABAA currents in rat sensory neurons. This study seeks to investigate the behavioral effects elicited by systemic administration of EpiP and to characterize its use as an adjuvant agent to commonly used general anesthetics (GAs). Methods: Here, we utilized electroencephalographic (EEG) recordings to characterize thalamocortical oscillations, as well as behavioral assessment and mouse genetics with wild-type (WT) and different knockout (KO) models of T-channel isoforms to investigate potential sedative/hypnotic and immobilizing properties of EpiP. Results: Consistent with increased oscillations in slower EEG frequencies, EpiP induced an hypnotic state in WT mice when injected alone intra-peritoneally (i.p.) and effectively facilitated anesthetic effects of isoflurane (ISO) and sevoflurane (SEVO). The CaV 3.1 (Cacna1g) KO mice demonstrated decreased sensitivity to EpiP-induced hypnosis when compared to WT mice, whereas no significant difference was noted between CaV 3.2 (Cacna1h), CaV 3.3 (Cacna1i) and WT mice. Finally, when compared to WT mice, onset of EpiP-induced hypnosis was delayed in CaV 3.2 KO mice but not in CaV 3.1 and CaV 3.3 KO mice. Conclusion: We posit that EpiP may have an important role as novel hypnotic and/or adjuvant to volatile anesthetic agents. We speculate that distinct hypnotic effects of EpiP across all three T-channel isoforms is due to their differential expression in thalamocortical circuitry. Highlights: This study seeks to investigate hypnotic effects of epipregnanolone (EpiP) and possible role of T-type calcium channels. EpiP induced hypnotic state in wild type (WT) mice and oscillations in slower electroencephalogram (EEG) frequencies. Only CaV 3.1, but not CaV 3.2 and CaV 3.3 KO mice showed decreased duration of EpiP-induced hypnosis when compared to WT mice. Onset of EpiP-induced hypnosis was delayed in CaV 3.2 KO mice but not in CaV 3.1 and CaV 3.3 KO mice when compared to WT mice. EpiP may have an important role as a novel sedative/hypnotic agent with distinct effects across all three T-channel isoforms.